Surface Plasmon‐Assisted Site‐Specific Cutting of Silver Nanowires Using Femtosecond Laser. Issue 2 (12th May 2016) - Fujita, Yasuhiko; Walke, Peter; Lu, Gang; Chamtouri, Maha; De Feyter, Steven; Uji‐i, Hiroshi
Abstract : Site‐specific cutting of chemically synthesized silver nanowires is demonstrated by simple focusing of a femtosecond laser. Structure and separation length of the cut‐ends can be controlled with sub‐micrometer resolution. Plasmonic wave‐guiding effect is conserved on the cut‐wires. This demonstrates that the method can be potentially useful for developing finer nanodevices based on chemically synthesized nanowires in a cost‐effective manner.